1993
DOI: 10.1073/pnas.90.21.10140
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Trypanosoma cruzi adenylyl cyclase by an alpha D-globin fragment from Triatoma hindgut: effect on differentiation of epimastigote to trypomastigote forms.

Abstract: A peptide from hindguts of the Triatoma hematophagous Chagas insect vector activates adenylyl cyclase activity in Trypanosoma cruzi epimastigote membranes and stimulates the in vitro differentiation of epimatigotes to metacyclic trypomastigotes. Hindguts were obtained from insects fed 2 days earlier with chicken blood. Purification was performed by gel fDtration and HPLC on Cis and C4 columns. SDS/PAGE of the purified peptide showed a single band of about 10 kDa. The foilowing sequence was determined for the 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
47
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 23 publications
4
47
1
Order By: Relevance
“…A PI-PLC activity was also detected in epimastigote lysates using PI as substrate (15). A synthetic peptide corresponding to a chicken ␣ D -globin fragment was able to increase inositol monophosphate (IP) and IP 3 levels in epimastigotes (16) and stimulate transformation of epimastigotes into trypomastigotes (metacyclogenesis) (17). A protein kinase C was also characterized in T. cruzi epimastigotes (18).…”
mentioning
confidence: 96%
“…A PI-PLC activity was also detected in epimastigote lysates using PI as substrate (15). A synthetic peptide corresponding to a chicken ␣ D -globin fragment was able to increase inositol monophosphate (IP) and IP 3 levels in epimastigotes (16) and stimulate transformation of epimastigotes into trypomastigotes (metacyclogenesis) (17). A protein kinase C was also characterized in T. cruzi epimastigotes (18).…”
mentioning
confidence: 96%
“…Several aspects on this subject are discussed by Azambuja et al (present Symposium). Fraidenraich et al (1993) isolated peptides from the hindgut of Triatoma infestans resulting from the digestion of a component of the α D -globin chain of chicken blood that are capable to induce the metacyclogenesis of T. cruzi in vitro. Later, Garcia et al (1995) demonstrated that differentiation of epimastigotes into metacyclic trypomastigotes in the insect's intestine is obtained if either hemoglobin or peptides corresponding to residues 30-49 and 35-73 of α D -globin chain are added to an infective plasma diet.…”
Section: Trypanosoma Cruzi and Triatomine Factorsmentioning
confidence: 99%
“…Fraidenraich and co-workers [22] showed that intestinal extracts of Triatoma infestans, containing peptides derived from hemoglobin breakdown, stimulated adenylate cyclase and induced metacyclogenesis. In addition, peptides released from the proteolysis of fibronectin increased cAMP levels in trypomastigotes [23].…”
Section: Trypanosoma Cruzimentioning
confidence: 99%